“Redemptive Reification” - Szabó, Anna (Hungarian Journal of English and American Studies, 2021)
Book review: Brown, Bill. Other Things. Chicago: Chicago UP, 2015. xiv + 396 pages. ISBN 9780026076652. Hb. 40.00